2022
DOI: 10.3389/fcvm.2022.981544
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Insights in cardiovascular therapeutics: 2021 – cell death, cardiovascular injuries, and novel targets of cardiovascular therapeutics

Abstract: and Yang X ( ) Editorial: Insights in cardiovascular therapeutics:cell death, cardiovascular injuries, and novel targets of cardiovascular therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Inflammasomes and inflammatory caspases, such as caspase-1 and caspase-4 (humans)/caspase-11 (mice), have two coupled functions: 1) serve as sensors for danger associated molecular patterns (DAMPs) and viral and bacterial infections-related pathogen associated molecular patterns (PAMPs) and 2) initiate inflammation signaling and promote inflammatory cell death (pyroptosis) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), which specifically antagonize infection but can cause detrimental inflammation as well (71). Recent studies have shown promise in treating NAFLD with therapeutics targeting the nucleotide-binding domain (NOD)-, leucine-rich repeat (LRR)and pyrin domain-containing protein 3 (NLRP3) inflammasome, suggesting that targeting pyroptosis is a viable option for treating the disease (72,73).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasomes and inflammatory caspases, such as caspase-1 and caspase-4 (humans)/caspase-11 (mice), have two coupled functions: 1) serve as sensors for danger associated molecular patterns (DAMPs) and viral and bacterial infections-related pathogen associated molecular patterns (PAMPs) and 2) initiate inflammation signaling and promote inflammatory cell death (pyroptosis) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), which specifically antagonize infection but can cause detrimental inflammation as well (71). Recent studies have shown promise in treating NAFLD with therapeutics targeting the nucleotide-binding domain (NOD)-, leucine-rich repeat (LRR)and pyrin domain-containing protein 3 (NLRP3) inflammasome, suggesting that targeting pyroptosis is a viable option for treating the disease (72,73).…”
Section: Introductionmentioning
confidence: 99%